Enhancing Students' Motivation and Learning Outcomes in Thematic Learning Using the Discovery Learning Model for Grade V SDN 31 Kinali - Sahari, Endang; Ayunis, Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to determine the increase in student motivation and learning outcomes in thematic learning using the Discovery Learning model for class V SDN 31 Kinali. This research aims to determine the increase in student motivation and learning outcomes in thematic learning using the Discovery Learning model for class V SDN 31 Kinali. Research subjects 18 students where 10 male students and 8 female students. This research was conducted in two cycles. In each cycle there are activities of planning, implementing, observing, and reflecting. Data collection techniques used observation and tests. The technique for checking the validity of the data used is source triangulation, namely comparing and re-checking the trustworthiness of data obtained through different times and tools by comparing the researcher's data with the learning results. The results of research using the Discovery Learning model can increase student motivation and learning outcomes. In cycle I, there were 5 students who completed with a percentage of 28%, while there were 13 students who did not complete with a percentage of 72%. In cycle II the number of students who completed was 15 people with a percentage of 83%, while there were 3 students who did not complete it with a percentage of 17%.